DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Kessler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie S; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif B; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
Keywords: cytoplazmatické dyneiny; Humans; Mutation; Protein Structure, Tertiary; Codon, Nonsense; Sequence Analysis, DNA; Cytoplasmic Dyneins; Fluorescent Antibody Technique; Exome; nesmyslný kodon; cilie; Cilia; heterozygot; exom; sekvenční analýza DNA; lidé; Heterozygote; fluorescenční protilátková technika; fibroblasty; mutace; Fibroblasts; terciární struktura proteinů